2002
DOI: 10.1124/jpet.102.034728
|View full text |Cite
|
Sign up to set email alerts
|

Piperine, a Major Constituent of Black Pepper, Inhibits Human P-glycoprotein and CYP3A4

Abstract: Dietary constituents (e.g., in grapefruit juice; NaCl) and phytochemicals (e.g., St. John's wort) are important agents modifying drug metabolism and transport and thereby contribute to interindividual variability in drug disposition. Most of these drug-food interactions are due to induction or inhibition of P-glycoprotein and/or CYP3A4. Preliminary data indicate that piperine, a major component of black pepper, inhibits drugmetabolizing enzymes in rodents and increases plasma concentrations of several drugs, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
304
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(312 citation statements)
references
References 39 publications
(52 reference statements)
6
304
1
1
Order By: Relevance
“…Indeed, piperine [53], ginsenosides [54,55], silymarin from milk thistle and other flavonoids [56], capsaicin [57], and resveratrol [57] were reported to inhibit P-gp activity in vitro, whereas curcumin [58,59] and curcuminoids [60] and several catechins from green tea [61][62][63] were shown to reduce P-gp expression and activity in vitro. Importantly, some of these herbal constituents (such as piperine, silymarin) have been observed to interact with P-gp at dietary concentrations, thus making a drug-herbal interaction in vivo more likely [53,56]. Similarly, constituents of grapefruit and orange juice were also found to block P-gp function and certain juice-drug interactions for commonly used drugs have been described too [64 -70].…”
Section: Inhibitors (Competitive Noncompetitive)mentioning
confidence: 99%
“…Indeed, piperine [53], ginsenosides [54,55], silymarin from milk thistle and other flavonoids [56], capsaicin [57], and resveratrol [57] were reported to inhibit P-gp activity in vitro, whereas curcumin [58,59] and curcuminoids [60] and several catechins from green tea [61][62][63] were shown to reduce P-gp expression and activity in vitro. Importantly, some of these herbal constituents (such as piperine, silymarin) have been observed to interact with P-gp at dietary concentrations, thus making a drug-herbal interaction in vivo more likely [53,56]. Similarly, constituents of grapefruit and orange juice were also found to block P-gp function and certain juice-drug interactions for commonly used drugs have been described too [64 -70].…”
Section: Inhibitors (Competitive Noncompetitive)mentioning
confidence: 99%
“…14 This strategy, however, should be used cautiously, as piperine is a potent inhibitor of drug metabolism and may cause toxicity in people taking specific drugs. 8,19,20 In addition, it is important to note that any strategy that increases the levels of curcumin in tissues will not only increase the effectiveness of curcumin, but also its toxicity.…”
Section: Dear Editormentioning
confidence: 99%
“…Literature concludes that piperine was used as effective bioavailability enhancer, inhibits the human P-glycoprotein and CYP3A4 a class of enzyme belonging to cytochrome P450 family [78] and enable the particular molecule to remain in biological system for much longer period. In various experimental studies, it has been shown that piperine when compounded with different molecules (drugs) enhances the bioavalibilty of β-lactumantibiotics [79,80], amoxicillin trihydrate and cefotaxime sodium [81], paeoniflorin [82], rifampicin [83,84], phenytoin [85], oxyphenolbutazone [86], nimesulide [87] and NSAIDS [88] or derivatives significantly.…”
Section: Piperine and Its Role In The Metabolism Of Xenobiotics In Thmentioning
confidence: 99%
“…Piperine, tetrahydropiperine, its analogs and derivatives also act as bioavailability enhancer of various nutrients including vitamins, β -carotene and selenium [78] and pharmaceuticals [91]. Various in vitro and in vivo studies concludes that the biotransformation of both water soluble and lipid soluble xenbiotics catalysed by pulmonary cytochrome P450 was likely to be affected or inhibited by presence of piperine [92].…”
Section: Piperine and Its Role In The Metabolism Of Xenobiotics In Thmentioning
confidence: 99%